Prosthechea: a chemical discontinuity in Laeliinae - Higgins, Wesley E. (Universidad de Costa Rica, 2016)
The chemistry of Prosthechea differs from other members of the subtribe. Williams (1979) was the first to report the unusual chemical properties of Prosthechea.